Complete rehabilitation of mouth cavity after early childhood caries treatment: A case report - Šurdilović Dušan; Shetty Manjunath Raghavendra (Medicinski fakultet i Klinika za stomatologiju, Niš, 2017)
Introduction: Early childhood caries (ECC) is a very serious public health problem in both developing and developed countries. We presented here a case of early childhood caries with full mouth rehabilitation. Case report: A five-and-a-half-year-old male patient accompanied by his mother reported to the department of pediatric dentistry with a chief complaint of severely decayed teeth. Intraoral examination revealed a set of mixed dentition with caries in relation to teeth 51, 52, 54, 55, 61, 62, 63, 64, 71, 72, 73, 81, 82, 84, 85 with some temporary dressing in teeth 74 and 75. Restoration with glass iomomeric cement on 71, 72, 81, 82, 83 tooth were done. Pulpectomy was done in relation to teeth 51, 52, 61, 62, 63, 74 and 75. Polyethylene fiber post (Ribbond) was placed in relation to teeth 51, 52, 61, 62 and 63. Final restoration with celluloid strip crowns in relation to teeth 51, 52, 61 and 62 were placed and composite restoration was done with tooth 63. Stainless steel crowns were placed on teeth 74, 75, 84 and 85. Conclusion: Full mouth rehabilitation of a child with early childhood caries is challenging for pediatric dentist. Oral rehabilitation also contributes to the improvement of general and psychological wellbeing of the child.